The Nitration of Monoalkyl Benzene and the Separation of its Isomers by Gas Chromatography - Rahmani, Mawardi (1982)
The nitronium ion, N02 +, is believed to be the attacking electrophile in the nitration reaction. When this reaction is carried out on monoalkyl substituted benzene, the substituents playa major role in determining the products obtained. The reaction also depends on the different methods of nitration employed. This report describes the method of determining the percentage of each isomer produced by gas chromatography.